Cortisol as Biomarker for Stress, Depression, And Physical Activity Among Medical Student: A Systematic Review - Pratama, Yanasta Yudo; Rismayanthi, Cerika; Rahayu, Atikah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Cortisol is one of the most commonly used stress biomarkers. Stress and depression are increasing in young people, especially among college students, especially medical students. Physical activity has been recommended for stress and depression relief, but its effect on cortisol has not been confirmed. This study aims to analyze cortisol measurements for stress, depression, their physical activity among medical student. This literature search utilized PubMed and Google Scholar, combining the keywords "cortisol", "stress", “depression”, “physical activity”, and "medical student" in publications from 2010 to 2025. Ten (10) studies that met our criteria. Most studies use saliva cortisol measurement to assess stress conditions. Our findings suggest cortisol as a measure of stress in medical students, but its contribution to the development of stress and depression remains unclear. There is no correlation between physical activity and cortisol in stress condition. Cortisol measurements can provide an objective test and reflect stress in medical students, but they do not adequately assess acute and stress-related cortisol release. Further studies are needed to assess the effectiveness of cortisol measurements.